Reteat on the Internet - Różański, Mieczysław; Krzyżak, Lesław (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The article shows a scientific approach which is rarely discussed. A legal and canonical analysis concerns a form of the proclamation of the Word of God which occurs during a retreat exercise. The article discusses etymology and a definition of retreat; retreat norms of universal law of the Church and the law of the particular Churches are invoked. The subject and content of the retreat are presented, their division (open, semi-open and closed) is made and then a possibility of practising retreat on the Internet is shown.